Tindak Pidana Penganiayaan Oleh Anak Di Bawah Umur Yang Dilakukan Oleh Lebih Dari Satu Orang Anak Yang Mengakibatkan Kematian Korban - Ahmad Zulfikar; Syarifa Mahila; Kemas Abdul Somad; S. Sahabuddin (Universitas Batanghari Jambi, 2022)
Criminal cases involving minors, such as abuse cases, are still being found. Criminal acts of maltreatment involving children, in particular criminal acts of abuse by minors committed by more than one child resulting in the death of the victim are not only categorized as reasonable delinquency, but have led to a crime. Lots of children commit acts of violence and thrown into prison or detention and often they are treated like adults. However, it is not uncommon for children who commit crimes not to be detained but to be fostered in child development institutions. This is because the juvenile criminal justice process has been regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System which prioritizes the settlement of legal issues involving children as perpetrators in the recovery and compensation experienced by victims from punishing children as perpetrators of crimes, but related to the act of a child committing maltreatment causing the death of another person, this matter needs to be considered.